1997
DOI: 10.1037/0021-843x.106.3.473
|View full text |Cite
|
Sign up to set email alerts
|

Antisocial personality disorder, conduct disorder, and substance abuse in schizophrenia.

Abstract: The validity of subtypes based on antisocial personality disorder (APD) or childhood conduct disorder without adult APD (CD only) in patients with schizophrenia (or schizoaffective disorder) and a substance use disorder (abuse or dependence) was examined. APD patients scored lower on personality measures related to socialization and higher on antisocial behavior, psychopathy, and aggression. APD patients also reported higher rates of aggression and legal problems. APD, and to a lesser extent CD only, was assoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
39
0
3

Year Published

2000
2000
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 18 publications
4
39
0
3
Order By: Relevance
“…In light of the findings that schizophrenia alone is associated with increased risks of physical aggression 12,15,26 and violent crime, 26 the present findings, if replicated, further circumscribe the type of aggressive behavior engaged in by men with schizophrenia. Many studies have shown an increased prevalence of physical aggression and violent crime by men with schizophrenia and any PD, 15 with antisocial PD, [26][27][28][29] with conduct disorder before 15 years of age, 30,31 and with SUDs. 32,33 Findings from the present study concur and extend previous findings by showing that schizophrenia plus a PD or an SUD was associated with an increased risk of any sexual offense and of physically aggressive sexual offenses.…”
Section: Commentmentioning
confidence: 99%
“…In light of the findings that schizophrenia alone is associated with increased risks of physical aggression 12,15,26 and violent crime, 26 the present findings, if replicated, further circumscribe the type of aggressive behavior engaged in by men with schizophrenia. Many studies have shown an increased prevalence of physical aggression and violent crime by men with schizophrenia and any PD, 15 with antisocial PD, [26][27][28][29] with conduct disorder before 15 years of age, 30,31 and with SUDs. 32,33 Findings from the present study concur and extend previous findings by showing that schizophrenia plus a PD or an SUD was associated with an increased risk of any sexual offense and of physically aggressive sexual offenses.…”
Section: Commentmentioning
confidence: 99%
“…3,[7][8][9] Although research on the effects of cannabis abuse on clinical parameters in individuals with schizophrenia has produced conflicting results, two prospective studies attempting to examine the longer-term outcome of cannabis use in this illness have both demonstrated poorer outcome and increased intensity of positive symptoms. 10,11 A number of prospective epidemiological studies also now provide support for the hypothesis that cannabis abuse increases the subsequent risk for developing schizophrenia.…”
mentioning
confidence: 99%
“…Pour Fulwiler et Ruthazer [26], ce serait plus la précocité de l'abus de substances indépendamment des troubles des conduites que l'abus de substances concomitant qui serait liée à la violence des personnes présentant une pathologie mentale. Or, la précocité de l'abus de substances pourrait dépendre de la présence d'une personnalité antisociale [66]. Indépendamment d'une pathologie mentale, abus d'alcool et personnalité antisociale auraient des similitudes étiogéniques, génétiques et environnementales [60].…”
Section: Importance Chronologiqueunclassified